Determining Critical Elements in Strengthening the Organisations: A Study on the Public Sector (Journal of Business Management and Accounting, 2015)
This paper presents the results of a case study conducted on three public sector organisations. The main objectives of this study were to identify critical elements which affect the organisations’ performance and to analyse competitive elements in organisations. The McKinsey 7S framework and the Kano Model were used to identify critical elements that need to be focused on in eachorganisation. The findings demonstrated that there are three elements that need to be finely thought-out in the formation and maintenance of the three public sector organisations. These elements are staff, structure, and skill. The results of the study can assist these organisations to clearly identify their organisational strengths and weaknesses. Accordingly, it helps in finding the middle ground to get all the elements into harmony that motivate the stimulation of highly effective functioning employees toward achieving better organisational performance.